COAL GEOCHEMISTRY OF THE UNCONVENTIONAL MUARAENIM COALBED RESERVOIR, SOUTH SUMATERA BASIN: A CASE STUDY FROM THE RAMBUTAN FIELD - Imam B. Sosrowidjojo (Indonesian Mining Journal, 2013)
Muaraenim coalbeds in Rambutan Field have typically high vitrinitic coal geochemical features that indicates the main target for CBM development. The presence of vitrinite coals in South Sumatra Basin is indicated by high huminite concentration (up to 83 vol.%). The coalbeds are of sub-bituminous rank (Ro<0.5%). They are geochemically characterized by high moisture content (up to 21%) and less than 80 wt.% (daf) carbon content. Minerals are found only in small amounts (<5 vol.%), mostly iron sulfide. Cleat fillings are dominated by kaolinite. This behavior can either be related to the increase coal moisture content to the depth or significant variation in vitrinite content within the deeper seams